2008
DOI: 10.1002/jcp.21368
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐rich plasma enhances the initial mobilization of circulation‐derived cells for tendon healing

Abstract: Circulation-derived cells play a crucial role in the healing processes of tissue. In early phases of tendon healing processes, circulation-derived cells temporarily exist in the wounded area to initiate the healing process and decrease in number with time. We assumed that a delay of time-dependent decrease in circulation-derived cells could improve the healing of tendons. In this study, we injected platelet-rich plasma (PRP) containing various kinds of growth factors into the wounded area of the patellar tendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
173
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(188 citation statements)
references
References 50 publications
5
173
0
4
Order By: Relevance
“…Releasate from platelet-rich plasma has been seen to activate circulation-derived cells [21] that play a crucial role in the tissue healing process and stimulate gene expression of the matrix molecules, collagen production and tendon cell proliferation [22]. In vitro studies demonstrated this mitogenic activity and that the stimulated tenocytes synthesise VEGF and HGF, thus suggesting a beneficial effect for the treatment of tendon injuries by inducing cell proliferation and promoting the synthesis of angiogenic factors during the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Releasate from platelet-rich plasma has been seen to activate circulation-derived cells [21] that play a crucial role in the tissue healing process and stimulate gene expression of the matrix molecules, collagen production and tendon cell proliferation [22]. In vitro studies demonstrated this mitogenic activity and that the stimulated tenocytes synthesise VEGF and HGF, thus suggesting a beneficial effect for the treatment of tendon injuries by inducing cell proliferation and promoting the synthesis of angiogenic factors during the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 PRP treatment of tendon disorders appeared to be effective in human and equine patients, [10][11][12] and studies using laboratory animals or in vitro methods have elucidated some of the working mechanisms. 8,9,13,14 Platelets are known to play a crucial role in the cascade of tissue healing by delivering growth factors to the site of injury. 15 Upon activation, platelets release growth factors, such as platelet-derived growth factor (PDGF), transforming growth factor (TGF)-b, vascular endothelial growth factor (VEGF), and insulin-like growth factor (IGF)-1, from their a-granules.…”
mentioning
confidence: 99%
“…More recently, PRP was used in human and equine sport medicine for therapy defects in ligaments and tendons (Mishra and Pavelko 2006;Arguelles et al 2008;Waselau et al 2008). A great advantage of autologous PRP therapy is the lack of immunological response in the treated organism (Kajikawa et al 2008).…”
mentioning
confidence: 99%